Effects of nutritional ergogenic aids on physiological responses and skilled performance among football players: a scoping review - Jariah, Muhammad Luqman (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia., 2021)
Introduction. – Football is known as the most popular sports in the world. In football, the need for macro-and micronutrients can be greatly increased by training and competition. Alternatively, these needs could be fulfilled by the football players by consuming supplements. Objective. - This review aimed to elucidate findings on recommended nutritional ergogenic aids to improve the physiological effects and sports performance among football players. Methodology. – Literature was searched systematically based on PRISMA guidelines, using Scopus, ScienceDirect, PubMed and ProQuest databases from year 2016 up to 2021. All 11 on human randomized-controlled trials studies were included in the final analysis. From the 11 studies reviewed, four studies were conducted to determine the effects of hydro electrolytic beverages while the remaining six studies were conducted using variety of beverages such as fruit drink, alcohol, caffeine, maltodextrin and probiotic. Results. – There were nine studies using drink types and the other two studies were using capsule types. The dosage of the supplements varies in all studies which ranges between 1 mg/kg BW to 4 mg/kg BW for capsuled supplement and between 0.48 ml/kg BW to 17.25 ml/kg BW for drink supplement. The supplements can be ingested at any time and at specific dosage depend on the purpose and aim of the participants. Carbohydrate-electrolyte solution or carbohydrate-electrolyte-protein solution ingestion (2 - 5 ml/kg BW) led to increase in some aspects of cognitive function. It is also found that some physiological responses such as plasma urea, aspartate aminotransferase and alanine aminotransferase improved after consumption of whey permeate with phenolic extract of jabuticaba peel. Another two studies using deep ocean mineral and CHO electrolyte increased in skilled performance such as high intensity running capacity, dribbling speed and other soccer specific performance. However, no differences in blood glucose and blood lactate concentration were observed. On the other hand, daily probiotic supplementation (3 ml/kg BW) in combination with regular food practice, training and competition for eight weeks resulted in better training, brain function, and physiological improvement to exercise. Non-alcoholic beer followed by steady-state exercise at 65% of HRmax for 45-min had maintained blood electrolyte homeostasis during exercise. Meanwhile, watermelon beverages (7 – 10 ml/kg BW) combined with Running-based Anaerobic Sprint Test (RAST) protocol resulted in reduction of fatigue index among football players and thus induced recovery phases. Isomaltulose or maltodextrin ingestion (4 – 6 ml/kg BW) led to increased blood glucose and no significant reduction in skilled performance. In addition, CHO intake (3 ml/kg BW) increased blood glucose, however it did not affect blood lactate and self-selected running performance or sprint times among football players. Anhydrous caffeine capsule (1 mg/kg BW) was ingested in combination with intermittent exercise protocol, leg strength and power and countermovement jump could enhance eccentric knee flexor performance but had no effect on physiological responses such as plasma glucose concentration, plasma insulin concentration, FFA concentration and USG. Meanwhile a combination of TeaCrine and caffeine (TCr + Caf) ingestion (4 mg/kg BW, capsule type) combined with four sessions of 90-min simulated treadmill soccer match was found to increase in running time-to-exhaustion and improved cognitive function. Conclusion. – The studies of supplementation in combination with exercise programme in this scoping review showed beneficial effects on some physiological responses and skilled performance among football players. It is believed that supplements could be taken as an ergogenic aid at pre, during and post exercise and the more popular form was drink types